Northern Akkad Project Reports. (Ghent, Belgium Ghent, Belgium Ghent, Belgium Ghent, Belgium)
<6> cilt (2. c. 70 sayfa, [1] katlı plan ; 4. c. 43 sayfa, [22] sayfa resim, çizim, şekil, harita, [1] katlı plan ; 5. c. 69 sayfa ; 7. c. 91 sayfa, [2] katlı plan ; 8. c. 77 sayfa ; 9. c. 61 sayfa)